Penerapan Play Therapy untuk Meningkatkan Perilaku Bersekolah pada Anak dengan School Refusal Behavior (SRB) - Esty Aryani Safithry (Anterior Jurnal, 2015)
This research aims to determine whether play therapy can improve the behavior of school children with school refusal behavior. This research used single case study. The subjects used in this research amounts to one person who has school refusal behavior. Methods of data collection using interviews, observation and documentation. Stages ofis divided into10 sessions of therapy sessions plus pre-treatment, post-treatment and follow-up. Results of this research showed improvement in school behavior at the time pre treatment only1 time a week to 6 times on a follow-up session.